Non-tuberculous mycobacterial disease: progress and advances in the development of novel candidate and repurposed drugs - Gu, Yuzhen; Nie, Wenjuan; Huang, Hairong; Yu, Xia (Frontiers in Cellular and Infection Microbiology, 2023)
Non-tuberculous mycobacteria (NTM) are opportunistic pathogens that can infect all body tissues and organs. In particular, the lungs are the most commonly involved organ, with NTM pulmonary diseases causing serious health issues in patients with underlying lung disease. Moreover, NTM infections have been steadily increasing worldwide in recent years. NTM are also naturally resistant to many antibiotics, specifically anti-tuberculosis (anti-TB) drugs. The lack of drugs targeting NTM infections and the increasing drug resistance of NTM have further made treating these mycobacterial diseases extremely difficult. The currently recommended NTM treatments rely on the extended indications of existing drugs, which underlines the difficulties of new antibiotic discovery against NTM. Another challenge is determining which drug combinations are most effective against NTM infection. To a certain extent, anti-NTM drug development depends on using already available antibiotics and compounds. Here, we aimed to review new antibiotics or compounds with good antibacterial activity against NTM, focusing on their mechanisms of action, in vitro and in vivo antibacterial activities.